(untitled) (Ágora Journal, 2025)
This article analyzes the urban proposal of the Novo Arrabalde, conceived between 1893 and 1896 by engineer Francisco Saturnino Rodrigues de Brito for the city of Vitória, in the state of Espírito Santo, during the first republican government of José de Mello Carvalho Moniz Freire (1892-1896). Drawing on Reinhart Koselleck’s analytical categories – space of experience and horizon of expectation – the article examines how the plan translated, through technical and symbolic language, the modernization ambitions of Brazil’s First Republic, combining sanitation, urban rationality, and landscape appreciation. Although never fully implemented, the project anticipated key principles that would shape the urban expansion of Vitória in the decades that followed. By confronting the institutional and economic limitations of the time with the symbolic persistence of the proposal, the study argues that the Novo Arrabalde embodied the tension between past and future in the field of urbanism. The article contributes to the historical understanding of urban planning in republican Brazil, highlighting the relationship between technical expertise, political agendas, and spatial construction.